2018
DOI: 10.1021/acs.estlett.8b00058
|View full text |Cite
|
Sign up to set email alerts
|

A Quantitative Model for the Coupled Kinetics of Arsenic Adsorption/Desorption and Oxidation on Manganese Oxides

Abstract: The ability to predict coupled kinetic reactions of arsenic (As) that occur at the manganese oxide–aqueous solution interface is crucial for management and remediation of As-contaminated sites worldwide. A quantitative understanding of the coupling between As oxidation and adsorption/desorption kinetics will enable us to more accurately predict the kinetic behavior of As. In this study, we developed a novel quantitative model for the coupled kinetics of As adsorption/desorption/oxidation on δ-MnO2. The kinetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(24 citation statements)
references
References 28 publications
1
23
0
Order By: Relevance
“…Completing this model is numerically difficult, due in part to rates spanning many orders of magnitude. The model developed by Feng et al (2018) takes a reductionist approach, and does not incorporate the role of Mn III in determining depletion rates [139]. While this approach can predict As(III) oxidation rates in a limited set of conditions, the resulting model parameters lose physical significance, as it does not incorporate steps in the known reaction mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Completing this model is numerically difficult, due in part to rates spanning many orders of magnitude. The model developed by Feng et al (2018) takes a reductionist approach, and does not incorporate the role of Mn III in determining depletion rates [139]. While this approach can predict As(III) oxidation rates in a limited set of conditions, the resulting model parameters lose physical significance, as it does not incorporate steps in the known reaction mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Arsenate adsorption and desorption significantly affected As redox kinetics on Mn oxides, which can be complicated by the competitive adsorption by Fe oxides. The model developed in this study can be further coupled into the As redox kinetics model as shown in our previous studies (Feng et al, 2018) to predict the coupled kinetics of As(III)/As(V) when multiple minerals are present. In addition, the structure and reactivity of ferrihydrite and MnO 2 may be affected by multiple biogeochemical factors, and our work based on the component additivity approach with mixed suspensions provided basis for understanding the As reactions with Fe‐Mn oxides formed in the field conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Quantitative understanding of the kinetics behavior and mechanisms of As(V) adsorption and desorption on soil minerals is of great significance for assessing the mobility and fate of As(III)/As(V) in the environment since the redox reactions of As species on soil minerals was usually coupled with the adsorption–desorption reactions (Feng et al, 2018; Lafferty et al, 2010b; Lan et al, 2018). Therefore, kinetics of As(V) adsorption–desorption on both ferrihydrite and δ‐MnO 2 had significant implications for the reactions of As species on mineral surfaces.…”
mentioning
confidence: 99%
See 2 more Smart Citations